Strategies to Overcome Intrinsic and Acquired Resistance to Chemoradiotherapy in Head and Neck Cancer - Tycho de Bakker; Anouk Maes; Tatiana Dragan; Philippe Martinive; Sébastien Penninckx; Dirk Van Gestel (Cells)
Definitive chemoradiotherapy (CRT) is a cornerstone of treatment for locoregionally advanced head and neck cancer (HNC). Research is ongoing on how to improve the tumor response to treatment and limit normal tissue toxicity. A major limitation in that regard is the growing occurrence of intrinsic or acquired treatment resistance in advanced cases. In this review, we will discuss how overexpression of efflux pumps, perturbation of apoptosis-related factors, increased expression of antioxidants, glucose metabolism, metallotheionein expression, increased DNA repair, cancer stem cells, epithelial-mesenchymal transition, non-coding RNA and the tumour microenvironment contribute towards resistance of HNC to chemotherapy and/or radiotherapy. These mechanisms have been investigated for years and been exploited for therapeutic gain in resistant patients, paving the way to the development of new promising drugs. Since in vitro studies on resistance requires a suitable model, we will also summarize published techniques and treatment schedules that have been shown to generate acquired resistance to chemo- and/or radiotherapy that most closely mimics the clinical scenario.